The Arrangement of the song Nyello' Aeng by Jaka Mahendra Hafizahrawani in the UL – Daul Lancenk Tresna music group, Pamekasan Regency - Louis Andika Budiono (Universitas Negeri Surabaya, 2026)
The song Nyello' Aeng tells of an activity carried out by villagers who still use or utilize water for their daily needs. The song Nyello' Aeng also tells the story of a village maiden and her activity, Nyello' Aeng, which in Indonesian means